Case Report: Lenalidomide as a Second-Line Treatment for Bortezomib-Ineffective Nephrotic Syndrome Caused by LCDD: 2 Case Reports and a Literature Review - Zhang, Xin; Yu, Xiao-juan; Wang, Su-xia; Zhou, Fu-de; Zhao, Ming-hui (Frontiers in Medicine, 2021)
Background Light-chain deposition disease (LCDD) is a rare systemic disorder characterized by the deposition of monoclonal light chains in organs. The kidney is a prominent target of light-chain deposition, with a median time to end-stage renal disease (ESRD) of 2.7 years and 5-year ESRD-free survival of 37%. The therapeutic management of LCDD remains ill-defined. In addition to bortezomib-based therapy as first-line therapy, the effect of lenalidomide on LCDD is rarely reported. Case presentation This study describes two male LCDD patients in their 60s with nephrotic syndrome and moderately impaired renal function. One patient had monoclonal IgGλ with underlying MGRS, and another had monoclonal IgGκ with underlying monoclonal gammopathy that developed into symptomatic MM during follow-up. The hallmarks of this disease were consistent with previous reports. Both patients initially received BCD therapy, but no hematological response was observed. Consequently, the nephrotic syndrome was refractory. Sequential Rd therapy was initiated, and partial hematological response and nephrotic remission were observed in the IgGλ patient but absent in the IgGκ patient. Conclusion Limited reports have demonstrated the effect of lenalidomide in LCDD. We report the outcome of lenalidomide in two cases of bortezomib-resistant LCDD. This treatment might be a beneficial supplement for those unresponsive or intolerant to bortezomib in LCDD, but the effect should be prospectively investigated.